Lactate Level Predicts Mortality in Patients with Upper Gastrointestinal Bleeding - Muge Gulen; Salim Satar; Adnan Tas; Akkan Avci; Hakan Nazik; Basak Toptas Firat (Gastroenterology Research and Practice)
Background and Objectives. The aim of this study was to show whether the level of lactate in venous blood compared with the Glasgow-Blatchford Bleeding Score (GBS), in patients diagnosed with upper gastrointestinal system (UGI) bleeding in the emergency department, will help to predict the need for transfusion and prognosis. Materials and Methods. Patients with UGI bleeding who were admitted to the emergency department were included in the study. The parameters age, gender, referral complaints, comorbidities, lactate levels in venous blood, GBS, endoscopy findings, length of hospital stay, transfusion amount, and outcome of patients were recorded in the data collection form. Results. A total of 139 patients were included in the study. The most common complaints were melena (38.1%) and hematemesis (32.4%). The most frequent endoscopic diagnosis was duodenal ulcer (40.3%). The cutoff value of the venous blood lactate level for the prediction of the need for red blood cell transfusion was 1.58 mmol/L, and the cutoff value for GBS was 9.5. While 124 patients were discharged, 15 patients died. The mean value of venous lactate in survived patients was 2.37 mmol/L and 4.80 in dead patients. This difference was statistically significant (p=0.044). The cutoff value of lactate for the prediction of mortality was 2.32 mmol/L, and the cutoff value for GBS was 13.5. Conclusions. The venous blood lactate value of a patient who was admitted to the emergency department with UGI bleeding might be helpful in predicting the transfusion needs of the patient and predicting the mortality.